2016
DOI: 10.1080/15374416.2016.1163707
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Habituation-Based Model of Exposures for Child and Adolescent Anxiety

Abstract: Exposure has been identified as key to effective treatment of youth anxiety. However, the precise theoretical mechanisms of exposure are a matter of debate. Emotional Processing Theory emphasizes the need for fear activation during exposure and its habituation both within and across exposures. Despite the popularity of the theory to explain exposure, it has not been tested with anxious youth. Objective To determine whether Emotional Processing Theory parameters predict anxiety severity, coping abilities, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 69 publications
2
29
1
Order By: Relevance
“…In contrast, the protocol evaluated in the present study emphasizes in-session exposures as a key component of the treatment. Prior work has shown that significant clinical improvement follow the introduction of exposure tasks during therapy (Peris et al, 2015) and are essential to treatment success (Bouchard, Mendlowitz, Coles, & Franklin, 2004; Hudson, 2005; Peterman, Carper, & Kendall, 2016; Rapee, Wignall, Hudson, & Schniering, 2000; Öst, Svensson, Hellstrom, & Lindwall, 2001). Assigning exposures solely as a homework exercise as opposed to a task to be completed under the guidance of the therapist in session, means that it is more difficult to know whether the child actually completed the exposure tasks and how well they were done.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the protocol evaluated in the present study emphasizes in-session exposures as a key component of the treatment. Prior work has shown that significant clinical improvement follow the introduction of exposure tasks during therapy (Peris et al, 2015) and are essential to treatment success (Bouchard, Mendlowitz, Coles, & Franklin, 2004; Hudson, 2005; Peterman, Carper, & Kendall, 2016; Rapee, Wignall, Hudson, & Schniering, 2000; Öst, Svensson, Hellstrom, & Lindwall, 2001). Assigning exposures solely as a homework exercise as opposed to a task to be completed under the guidance of the therapist in session, means that it is more difficult to know whether the child actually completed the exposure tasks and how well they were done.…”
Section: Discussionmentioning
confidence: 99%
“…There is now little support for within-session fear reduction, and stronger but mixed support for between-session fear reduction, as predictors of treatment outcomes in exposure therapy for adults (Asnaani et al, in press; Craske et al, 2008) and youth (Peterman, Carper, & Kendall, in press), as well as in written forms of exposure (Wisco, Baker, & Sloan, 2015). Further, there is some evidence that even clients who do not experience fear reduction over time can improve by learning to tolerate their distress and change the meaning of that distress (Bluett et al, 2014; Craske et al, 2008; Zvolensky, Vujanovic, Bernstein, & Leyro 2010).…”
mentioning
confidence: 99%
“…Habituation is characterised by the decrease in arousal experienced from repeated exposure to a stimulus (Cyr & Romero, 25 LAY REPRESENTATIONS OF HABIT 2009;Thompson & Spencer, 1966). The process of habituation is purposefully used in exposure therapy for anxiety disorders, whereby patients are repeatedly exposed to feared stimuli to reduce their fear arousal in the stimuli's presence (Cooper, Clifton, & Feeny, 2017;Peterman, Carper, & Kendall, 2019). However, a version of this process may similarly apply to everyday habitual behaviours, promoting the feeling of familiarity when performing the habitual behaviour and provoking a stress-response if not performed.…”
Section: Discussionmentioning
confidence: 99%